Rhodotorula infection in haematological patient: Risk factors and outcome. Issue 3 (28th December 2018) - Potenza, Leonardo; Chitasombat, Maria N.; Klimko, Nikolay; Bettelli, Francesca; Dragonetti, Giulia; Del Principe, Maria Ilaria; Nucci, Marcio; Busca, Alessandro; Fracchiolla, Nicola; Sciumè, Mariarita; Spolzino, Angelica; Delia, Mario; et al.
Summary: Background: Rhodotorula spp are uncommon yeasts able to cause infections with high mortality rates. Rhodotorula infections have been associated with the presence of central venous catheter (CVC), immunosuppression, exposure to antifungals and the presence of either solid or haematologic malignancies. However, in this latter setting, only a few cases have so far been reported. Objectives: We have conducted a survey for Rhodotorula infections in haematologic patients. Methods: Patients' clinical and microbiological data were collected and correlated to the outcome. Results: A total of 27 cases were detected from 13 tertiary care hospitals. About 78% and 89% of patients had acute leukaemia and CVC. About 70% of patients were exposed to prophylaxis with azoles, mainly posaconazole (37%), 59% were severely neutropenic and 37% underwent allogeneic stem cell transplantation (alloSCT). The most frequent treatments were liposomal amphotericin B (L‐AmB) and CVC removal in 17 and 16 patients, respectively. One month post‐diagnosis, mortality was 26% and was associated with the presence of mucositis ( P  = 0.034). Conclusions: Our study shows that Rhodotorula spp should be considered as aetiologic agents of breakthrough infections in acute leukaemia patients with a CVC, mucositis, who receive prophylaxis with azoles, including posaconazole, and/or undergo alloSCT. Prompt measures, such as L‐AmB administration and CVC removal, should be carried out to avoid the high mortality risk of Rhodotorula infections.